High-temperature-resistant and wear-resistant laser cladding alloy coating powder and application thereof
By mixing aerosolized Ni-RE high-temperature alloy powder and hard phase powder and preparing the coating using laser cladding process, the problem of degradation of wear resistance of Inconel 718 alloy at high temperatures is solved, and its wear resistance, corrosion resistance and oxidation resistance at high temperatures is significantly improved.
Patent Information
- Application Number
- CN202411806180.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
Inconel 718 alloy is prone to oxidative wear in high temperature environments, especially when it is between 700°C and 800°C and above, its wear resistance is significantly reduced, limiting its application in higher temperature environments.
Aerosolized Ni-RE high-temperature alloy powder and hard phase powder are mixed with mass ratio (97-99): (1-3), and the high-temperature wear-resistant laser clad alloy coating powder is prepared, and it is clad on the surface of the metal substrate through a laser clading process, and heat treatment and grinding are carried out.
It significantly improves the wear resistance, corrosion resistance and high-temperature oxidation resistance of Inconel 718 alloy at high temperatures, and extends its service life in high-temperature environments.
Smart Images

Figure CN119640256A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material surface repair, and in particular to a high-temperature-resistant and wear-resistant laser cladding alloy coating powder and application thereof. Background Art
[0002] Laser cladding is a surface modification technology with high energy density and high processing precision. It is suitable for most metal materials. This technology uses a high-energy laser beam to act on the cladding material (generally metal powder) to quickly melt and solidify the cladding material and the substrate surface material in a local area to form a good metallurgical bond. Laser cladding coating materials mainly use Fe-based, Co-based, and Ni-based self-fluxing alloy powders. Among them, although the Fe-based alloy coating has high hardness and corrosion resistance and a low price, it is prone to defects such as cracks and pores during the cladding process; the Co-based powder coating has excellent high temperature resistance and corrosion resistance, but it is expensive; the Ni-based powder coating not only has high hardness, wear resistance, high temperature resistance and corrosion resistance, but also has a moderate price, so it has been widely used.
[0003] Inconel 718 alloy is a high-temperature resistant nickel-based alloy widely used in aerospace, energy, chemical and other fields. The alloy has excellent mechanical properties and environmental adaptability in high temperature environments, especially below 650°C, and is particularly stable, so it has become an important manufacturing material in high-temperature fields such as gas turbines, nuclear energy and petrochemicals. However, with the rapid development of industrial technology, more and more mechanical moving parts need to serve under extremely harsh conditions such as high temperature, high speed, high load and special environment, which puts higher requirements on the high-temperature mechanical properties, high-temperature oxidation resistance and wear resistance of materials. Friction and wear tests show that Inconel 718 alloy is more susceptible to oxidation wear at high temperatures, especially at 700°C to 800°C and above, its wear resistance decreases significantly, thus limiting its application in higher temperature environments. Therefore, it is particularly important to carry out surface strengthening treatment to improve the wear resistance of Inconel 718 alloy at high temperatures. Summary of the invention
[0004] In view of the above-mentioned prior art, the purpose of the present invention is to provide a high temperature and wear resistant laser cladding alloy coating powder and application thereof.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] In a first aspect of the present invention, a high temperature and wear resistant laser cladding alloy coating powder is provided, which is prepared by mixing atomized Ni-RE high temperature alloy powder and hard phase powder in a mass ratio of (97-99): (1-3);
[0007] The gas atomized Ni-RE high temperature alloy powder is prepared from Inconel 718 alloy powder and rare earth elements in a mass ratio of (99.8-99.98): (0.02-0.2);
[0008] The rare earth element is one or more of La, Ce, and Y;
[0009] The hard phase powder consists of Al2O3, TiO2 and WC.
[0010] Preferably, the hard phase powder is composed of Al2O3, TiO2 and WC in a mass ratio of (30-50):(5-15):(15-30).
[0011] Preferably, the gas atomized Ni-RE high temperature alloy powder is prepared from Inconel 718 alloy and rare earth elements in a mass ratio of 99.9:0.1.
[0012] Preferably, the rare earth elements are composed of yttrium and cerium in a mass ratio of (2-4):(1-3).
[0013] Preferably, the gas atomized Ni-RE high temperature alloy powder is prepared by the following method:
[0014] Inconel 718 alloy and rare earth oxides are used as raw materials, and smelting, degassing and atomization are carried out under high-purity argon to obtain gas-atomized Ni-RE high-temperature alloy powder.
[0015] Preferably, the melting temperature is 1550-1590°C, and the time is 40-60 min; the degassing temperature is 1590-1600°C, and the time is 5-10 min; the atomization temperature is 1600-1680°C, the atomization pressure is 3.5-4.5 MPa, and the time is 15-25 min.
[0016] Preferably, the particle size of the gas atomized Ni-RE high temperature alloy powder is in the range of 35 to 53 μm; and the particle size of the hard phase powder is in the range of 40 to 55 μm.
[0017] The second aspect of the present invention provides the use of the above-mentioned high temperature and wear-resistant laser cladding alloy coating powder in the preparation of high temperature and wear-resistant laser cladding coating.
[0018] A third aspect of the present invention provides a method for preparing a high temperature and wear resistant laser cladding coating using the above-mentioned high temperature and wear resistant laser cladding alloy coating powder, comprising the following steps:
[0019] The high temperature and wear resistant laser cladding alloy coating powder is clad on the surface of the metal substrate by laser cladding process, and the metal substrate after laser cladding is subjected to heat treatment and lathing to form a high temperature and wear resistant laser cladding coating;
[0020] Laser cladding process parameters are:
[0021] The laser power is 1500-2000W; the spot diameter is 2.5mm; the cladding speed is 2500-3500mm / min; the powder feeding speed is 25-35mg / s; the overlap rate is 40%-50%; high-purity argon is used as the protective gas, and the gas flow rate is 10-20L / min.
[0022] Preferably, the heat treatment temperature is 180-220° C., and the heat treatment time is 0.4-1.0 h.
[0023] Preferably, the metal substrate is a 45 steel round bar with a diameter of 74 mm.
[0024] Beneficial effects of the present invention:
[0025] 1. The present invention modifies nickel-based high-temperature alloy powder, which is a type of alloy material that can work reliably for a long time under complex stress environments above 600°C. The present invention adds rare earth elements Ce and Y to the high-temperature alloy powder, and applies rare earth elements in laser cladding technology, which is beneficial to improving the surface structure morphology of the cladding layer and improving the mechanical properties, can optimize the microstructure of the organization, inhibit the generation of cracks in the cladding layer, and refine the grains, and has a significant effect on improving the mechanical properties, wear resistance, corrosion resistance and high-temperature oxidation resistance of the cladding layer. At the same time, the optimized high-temperature alloy powder is uniformly mixed with Al2O3, TiO2 and WC, and the metal ceramic phase not only has high hardness and strength, but also softens at high temperatures and has low shear strength to show lubrication, and can reduce the wear rate of the friction pair, which plays a vital role in reducing the friction coefficient and wear rate.
[0026] 2. The laser cladding prepared by the present invention can be widely used in the petroleum industry. The coating has extremely strong wear resistance and high temperature resistance, and can meet the industry's requirements for the performance of laser cladding coatings under special conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a metallographic microscope image of the microstructure of the laser cladding coating in Example 2 of the present invention;
[0028] Figure 2 This is a metallographic microscope image of the microstructure of the laser cladding coating in Comparative Example 1 of the present invention;
[0029] Figure 3 This is a metallographic microscope image of the microstructure of the laser cladding coating in Comparative Example 2 of the present invention;
[0030] Figure 4This is a metallographic microscope image of the microstructure of the laser cladding coating in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0031] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0032] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.
[0033] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.
[0034] The Inconel 718 alloy used in the present invention is a purchased existing alloy, and its composition is:
[0035] Cr is 17.0~21.0%, Ni is 50.0~55.0%, C is 0.02~0.08%, Fe is 15.0~21.0%, Mo is 2.8~3.3%, Nb is 4.75~5.45%, Al is 0.3~0.7%, Ti is 0.85~1.15%, Co≤1.0%, B≤0.006%, Mn≤0.35%, P≤0.015%, S≤0.003%, Cu≤0.20%, Ta≤0.05%, Si≤0.15%, N≤0.02%, and O≤0.02%.
[0036] Example 1: Preparation of high temperature and wear resistant laser cladding alloy coating powder:
[0037] (1) Raw material composition (mass percentage): 97% gas atomized Ni-RE high temperature alloy powder and 3% hard phase powder;
[0038] The gas atomized Ni-RE high temperature alloy powder is prepared from Inconel 718 alloy and rare earth elements in a mass ratio of 99.9:0.1; the rare earth elements are composed of yttrium and cerium in a mass ratio of 3:2;
[0039] The hard phase powder is a mixture of Al2O3, TiO2 and WC in a mass ratio of 4:1:2;
[0040] The particle size of the gas atomized Ni-RE high temperature alloy powder ranges from 35 to 53 μm; the particle size of the hard phase powder ranges from 40 to 55 μm;
[0041] (2) Preparation of gas atomized Ni-RE high temperature alloy powder:
[0042] Inconel 718 alloy, yttrium oxide and cerium oxide are used as raw materials, and smelting, degassing and atomization are carried out under high-purity argon to obtain gas-atomized Ni-RE high-temperature alloy powder;
[0043] The melting temperature is 1570℃, the time is 50min; the degassing temperature is 1595℃, the time is 8min; the atomization temperature is 1640℃, the atomization pressure is 4.0Mpa, and the time is 20min;
[0044] (3) Weighing atomized Ni-RE high temperature alloy powder and hard phase powder according to a certain proportion, and evenly mixing them to obtain high temperature and wear resistant laser cladding alloy coating powder.
[0045] Example 2: Preparation of high temperature and wear resistant laser cladding coating:
[0046] The high temperature and wear resistant laser cladding coating described in this embodiment adopts a synchronous powder feeding method, and uses a fiber laser to form a cladding layer on the surface of the substrate. The specific steps are as follows:
[0047] (1) Pretreatment of metal substrate: first use a grinder to remove the oxide layer on the surface of the substrate, then put the substrate into anhydrous ethanol for ultrasonic cleaning to remove surface oil, and then put the substrate into a vacuum drying oven for drying; dry the powder and sieve it;
[0048] (2) using a laser cladding process to clad the high temperature and wear resistant laser cladding alloy coating powder prepared in Example 1 on the surface of a metal substrate;
[0049] In the above steps, the metal substrate selected is a 45 steel round bar with a diameter of 74 mm;
[0050] The fiber laser was used, and the selected laser cladding process parameters were: laser power of 1800W; spot diameter of 2.5mm; cladding speed of 3000mm / min; powder feeding speed of 30mg / s; overlap rate of 40%; high-purity argon was used as the protective gas, and the gas flow rate was 15L / min;
[0051] (3) The metal substrate after laser cladding is subjected to heat treatment and lathing at a heat treatment temperature of 200° C. for a heat treatment time of 0.5 h to form a laser cladding coating with a cladding layer thickness of 1.25 mm.
[0052] The microstructure of the laser cladding coating in this embodiment is as follows: Figure 1 As shown, it can be found that due to the presence of rare earth elements, a certain proportion of equiaxed crystals are formed on the coating surface with the largest temperature supercooling. At the same time, the dispersion effect of the hard phase is improved, forming a uniform organizational structure, which is beneficial to improving the mechanical properties of the product.
[0053] Comparative Example 1:
[0054] The difference between this comparative example and Example 2 is:
[0055] Laser cladding alloy coating powder is prepared by the following method:
[0056] (1) Raw material composition (mass percentage): 97% gas atomized Inconel 718 alloy powder and 3% hard phase powder;
[0057] The hard phase powder is a mixture of Al2O3, TiO2 and WC in a mass ratio of 4:1:2;
[0058] The particle size range of gas atomized Inconel 718 alloy powder is 35-53 μm; the particle size range of hard phase powder is 40-55 μm;
[0059] (2) Gas atomized Inconel 718 alloy powder was prepared by the following method:
[0060] Inconel 718 alloy was used as raw material, and smelting, degassing and atomization were carried out under high-purity argon to obtain gas-atomized Ni-RE high-temperature alloy powder;
[0061] The melting temperature is 1570℃, the time is 50min; the degassing temperature is 1595℃, the time is 8min; the atomization temperature is 1640℃, the atomization pressure is 4.0Mpa, and the time is 20min;
[0062] (3) Weigh the gas atomized Inconel 718 alloy powder and the hard phase powder according to the proportion, mix them evenly and obtain the laser cladding alloy coating powder.
[0063] The difference between this comparative example and Example 1 is that the prepared laser cladding alloy coating powder does not contain rare earth elements, and is composed of gas atomized Inconel 718 alloy powder and hard phase powder.
[0064] According to the method of Example 2, the prepared laser cladding alloy coating powder was used to prepare a 1.25 mm thick laser cladding coating on the surface of a metal substrate.
[0065] The microstructure of the laser cladding coating in this comparative example is as follows Figure 2 As shown, it can be found that due to the influence of the added hard phase powder on the supercooling of the components, relatively fine columnar crystals are formed, and the grain boundaries are the added hard phase.
[0066] Comparative Example 2:
[0067] The difference between this comparative example and Example 2 is:
[0068] Laser cladding alloy coating powder is prepared by the following method:
[0069] (1) Raw material composition: gas atomized Ni-RE high temperature alloy powder;
[0070] The gas atomized Ni-RE high temperature alloy powder is prepared from Inconel 718 alloy and rare earth elements in a mass ratio of 99.9:0.1; the rare earth elements are composed of yttrium and cerium in a mass ratio of 3:2;
[0071] The particle size range of gas atomized Ni-RE superalloy powder is 35 to 53 μm;
[0072] (2) Preparation of gas atomized Ni-RE high temperature alloy powder:
[0073] Inconel 718 alloy, yttrium oxide and cerium oxide are used as raw materials, and smelting, degassing and atomization are carried out under high-purity argon to obtain gas-atomized Ni-RE high-temperature alloy powder;
[0074] The melting temperature is 1570℃, the time is 50min; the degassing temperature is 1595℃, the time is 8min; the atomization temperature is 1640℃, the atomization pressure is 4.0Mpa, and the time is 20min;
[0075] The difference between this comparative example and Example 1 is that the prepared laser cladding alloy coating powder does not contain a hard phase and is composed of 100% gas atomized Ni-RE high temperature alloy powder.
[0076] According to the method of Example 2, the prepared laser cladding alloy coating powder was used to prepare a 1.25 mm thick laser cladding coating on the surface of a metal substrate.
[0077] The microstructure of the laser cladding coating in this comparative example is as follows Figure 3 As shown, it can be found that although no hard phase is added, the presence of rare earth elements also has a positive effect on the reduction of grain size.
[0078] Comparative Example 3:
[0079] The difference between this comparative example and Example 2 is:
[0080] Laser cladding alloy coating powder is prepared by the following method:
[0081] The difference between this comparative example and Example 1 is that the laser cladding alloy coating powder uses a single gas atomized Inconel718 alloy powder;
[0082] Gas atomized Inconel 718 alloy powder is prepared by the following method:
[0083] Inconel 718 alloy is used as raw material, and smelting, degassing and atomization are carried out under high-purity argon to obtain gas-atomized Ni-based high-temperature alloy powder;
[0084] The melting temperature is 1570°C and the time is 50 min; the degassing temperature is 1595°C and the time is 8 min; the atomization temperature is 1640°C, the atomization pressure is 4.0 MPa and the time is 20 min.
[0085] According to the method of Example 2, the prepared laser cladding alloy coating powder was used to prepare a 1.25 mm thick laser cladding coating on the surface of a metal substrate.
[0086] The microstructure of the laser cladding coating in this comparative example is as follows Figure 4 As shown, it can be found that due to the lack of rare earth elements and hard phases, there are more dendrites in the coating, so the mechanical properties and wear resistance of the coating are relatively poor.
[0087] Test example:
[0088] 1. Wear tests were carried out in accordance with ISO 20808. The laser cladding coatings prepared in Example 2 and Comparative Examples 1-3 were rubbed against Si3N4 ceramic balls at 800°C. The friction sample size was a φ25mm×5mm disc, the diameter of the Si3N4 ceramic ball was 10mm, the sliding speed was 0.1m / s, the friction distance was 2000m, and the applied load was 10N. The average friction coefficient and wear rate were measured by experiments. The experimental results are shown in Table 1.
[0089] 2. Wear tests were carried out in accordance with ISO 20808. The laser cladding coatings prepared in Example 2 and Comparative Example 3 were rubbed against Si3N4 ceramic balls at different temperatures (700°C, 800°C and 900°C). The average friction coefficient and wear rate were measured. The experimental results are shown in Table 2.
[0090] Table 1 Wear of laser cladding coatings in different treatment groups
[0091]
[0092]
[0093] It can be seen from Table 1 that the laser cladding coating prepared in Example 2 exhibits particularly high temperature resistance and wear resistance, while both Comparative Example 3 and Comparative Example 1 suffer obvious wear damage.
[0094] Table 2 Wear of laser cladding coatings at different treatment temperatures
[0095]
[0096] It can be seen from Table 2 that the wear resistance of the single IN718 alloy is significantly reduced, but the present invention still has good wear resistance at a higher temperature (900° C.) through modification.
[0097] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A high temperature and wear resistant laser cladding alloy coating powder, characterized in that: The gas atomized Ni-RE high temperature alloy powder and the hard phase powder are mixed in a mass ratio of (97-99): (1-3); The gas atomized Ni-RE high temperature alloy powder is prepared from Inconel 718 alloy powder and rare earth elements in a mass ratio of (99.8-99.98): (0.02-0.2); The rare earth element is one or more of La, Ce, and Y; The hard phase powder consists of Al2O3, TiO2 and WC.
2. The high temperature and wear resistant laser cladding alloy coating powder according to claim 1, characterized in that: The hard phase powder is composed of Al2O3, TiO2 and WC in a mass ratio of (30-50): (5-15): (15-30).
3. The high temperature and wear resistant laser cladding alloy coating powder according to claim 1, characterized in that: The gas atomized Ni-RE high temperature alloy powder is prepared from Inconel 718 alloy powder and rare earth elements in a mass ratio of 99.9:0.
1.
4. The high temperature and wear resistant laser cladding alloy coating powder according to claim 1 or 3, characterized in that: The rare earth elements are composed of yttrium and cerium in a mass ratio of (2-4): (1-3).
5. The high temperature and wear resistant laser cladding alloy coating powder according to claim 1 or 4, characterized in that: The gas atomized Ni-RE high temperature alloy powder is prepared by the following method: Inconel 718 alloy and rare earth oxides are used as raw materials, and smelting, degassing and atomization are carried out under high-purity argon to obtain gas-atomized Ni-RE high-temperature alloy powder.
6. The high temperature and wear resistant laser cladding alloy coating powder according to claim 5, characterized in that: The melting temperature is 1550-1590°C, and the time is 40-60 min; the degassing temperature is 1590-1600°C, and the time is 5-10 min; the atomization temperature is 1600-1680°C, the atomization pressure is 3.5-4.5 MPa, and the time is 15-25 min.
7. The high temperature and wear resistant laser cladding alloy coating powder according to claim 1, characterized in that: The particle size of the gas atomized Ni-RE high temperature alloy powder is in the range of 35 to 53 μm; the particle size of the hard phase powder is in the range of 40 to 55 μm.
8. Use of the high temperature and wear resistant laser cladding alloy coating powder according to any one of claims 1 to 7 in the preparation of high temperature and wear resistant laser cladding coatings.
9. A method for preparing a high temperature and wear resistant laser cladding coating using the high temperature and wear resistant laser cladding alloy coating powder according to any one of claims 1 to 7, characterized in that: The following steps are involved: The high temperature and wear resistant laser cladding alloy coating powder according to any one of claims 1 to 7 is clad on the surface of a metal substrate by a laser cladding process, and the metal substrate after laser cladding is subjected to heat treatment and lathing to form a high temperature and wear resistant laser cladding coating; Laser cladding process parameters are: The laser power is 1500-2000W; the spot diameter is 2.5mm; the cladding speed is 2500-3500mm / min; the powder feeding speed is 25-35mg / s; the overlap rate is 40%-50%; high-purity argon is used as the protective gas, and the gas flow rate is 10-20L / min.
10. The method according to claim 9, characterized in that The heat treatment temperature is 180-220°C, and the heat treatment time is 0.4-1h.